Quality Improvement of Mangosteen for Export Through Drip Irrigation System and Yellow Fluorescent Sticky Trap Installation - Affandi Affandi; Liza Octriana; Dewi Fatria; Titin Purnama (AGRIVITA Journal of Agricultural Science, 2011)
Mangosteen (Garcinia mangostana Linn.) dubbed as “finest fruit of the world”, has potential for both domestic market and export. However, this potential is threatened by low fruit quality caused by production of yellow latex and fruit scarring. The research objective was to obtain technology to reduce yellow latex and control Scirtothrips dorsalis, a pest that causes scarring on mangosteen. A randomized block design with four treatments and 14 replications was used in this research. Significant differences among the treatments were calculated using the Honestly Significant Difference (HSD) test. The results showed that treatment of drip irrigation system in combination with removing weeds under the canopy (A) or removing weeds followed by minimum tillage under the canopy (B) or removing weeds then covering with rice hay mulch under the canopy (C), where N, P, K, Ca, Mg fertilizer and yellow fluorescent sticky trap were applied could reduce scarring intensity and percentage of yellow latex on the fruit peel. However, the treatments did not significantly impact fruit diameter or percentage of yellow latex inside the fruit. Nevertheless, treatment C improved mangosteen quality by as much as 67.79% fulfilling export standard requirements.Keywords: Mangosteen, quality improvement, drip irrigation, yellow fluorescent sticky trap